Effects of COVID-19 Virus Infection on Pregnancy Outcomes: a Systematic Review and Meta-analysis - Pandit, Upendra; Shrestha, Niki; Khanal, Gayatri (Journal of Nepal Health Research Council, 2023)
Background: Pregnant mothers are more susceptible to Corona Virus Diseases 2019 (COVID-19) during pandemic. Our aim was to find out the effects of the COVID-19 infection on pregnancy outcomes compared to mothers without COVID-19 diseases. Methods: The review protocol was registered in the International Prospective Register of Systematic Reviews (PROSPERO) and obtained number of the Centre for review and Dissemination (CRD42021272321). The observational studies from September 1st to October 31, 2021 were searched with Medical Subject Heading (MeSH) term in the databases. A Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guideline was followed. Certainty of the evidence were assessed using Grading of Recommendations Assessment Development and Evaluation (GRADEpro) approach. Results: Pregnant women with Polymerase Chain Reaction (PCR) positive group for COVID-19 were likely to have preeclampsia/eclampsia of Relative Risk (RR) and Confidence Interval (CI) (RR, 1.52; 95% CI, 1.14-2.02) respectively. Likewise, foetal distress (RR, 1.56; 95% CI, 1.31- 1.85, caesarean section (RR, 1.25; 95% CI, 1.10-1.42), postpartum haemorrhage (RR, 1.37; 95%CI, 1.00-1.88), moderate certainty of the evidence in ICU/high-dependency unit admission (RR, 4.92; 95% CI, 3.28- 7.38), preterm births (RR, 2.12; 95% CI, 1.10-4.08) and perinatal death (RR, 2.55; 95% CI, 1.64-3.95). Very wide CI on maternal death rate (RR 9.87; 95% CI, 3.10- 31.45) was observed compared to COVID-19 negative group. Conclusions: Pregnant mothers with COVID-19 positive diseases have a moderate certainty of the effect of admission to ICU/high-dependency unit, Preterm birth and perinatal death. Keywords: Childbirth; complications; COVID-19; maternal; neonates